Tinjauan Hukum Pertanggung Jawaban Penggunaan Munisi Tandan (Cluster Bom) dalam Hukum Humaniter Internasional Berdasarakan Convention On Cluster Munition 2008 - Ike Angrayni; Evi Deliana; Aditiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
International Humanitarian Law is part of the International Law which deals with human treatment in one situation, especially in times of conflict. This means, before international humanitarian law was developed, there was no rule of law concerning regulation in time of war. One regulated in humanitarian law is to limit the use of armed forces in warfare on the basis of the principle of proportionality and discrimination. which is the type of weapon is very dangerous for humanity, one of these weapons is cluster munition, cluster munition is A conventional powder designed to disperse or release explosive submunitions each weighing less than 20 kilograms, and including explosive explosives . Another term from it is cluster bombs or cluster bombs, because many countries are concerned about the use of these weapons, a convention on cluster munition was established in 2008 in Oslo, which regulates the use of cluster munitionsThe problem posed in this paper is about the a legal review of usage cluster munition ands review of Cluster Bomb's Law of Accountability in International Humanitarian Law based on Convention On Cluster Munition 2008, this type of research is normative legal research that examines the law based on its principles.From this research, it can be known that firstly, the use of cluster munitions or cluster bombs is very dangerous because this bomb can switch function as a land mine that can endanger civilians and can threaten Human Rights every person, second, every State has signed a convention on cluster munition shall comply with the contents of the convention which governs the State's accountability of the use of cluster munitions.Keywords : Cluster Munition, Convention on Cluster Munition 2008, State Responsibility